Escrita e identidades (Cadernos de Linguagem e Sociedade, 2010)
The focus of this paper is on gender identities at work place adult literacy. Based on the concept of discourse as a crucial dimension of social practices in relation to other dimensions, mainly power, the paper addresses the issue of identity change in past narratives and their recontextualisation associated with work place current demands. The research findings suggest that women and men use different strategies in relation to literacy.